WNK signalling pathways in blood pressure regulation - Murthy, Meena; Kurz, Thimo; O’Shaughnessy, Kevin M. (Cellular and molecular life sciences : CMLS, 2017)
Hypertension (high blood pressure) is a major public health problem affecting more than a billion people worldwide with complications, including stroke, heart failure and kidney failure. The regulation of blood pressure is multifactorial reflecting genetic susceptibility, in utero environment and external factors such as obesity and salt intake. In keeping with Arthur Guyton’s hypothesis, the kidney plays a key role in blood pressure control and data from clinical studies; physiology and genetics have shown that hypertension is driven a failure of the kidney to excrete excess salt at normal levels of blood pressure. There is a number of rare Mendelian blood pressure syndromes, which have shed light on the molecular mechanisms involved in dysregulated ion transport in the distal kidney. One in particular is Familial hyperkalemic hypertension (FHHt), an autosomal dominant monogenic form of hypertension characterised by high blood pressure, hyperkalemia, hyperchloremic metabolic acidosis, and hypercalciuria. The clinical signs of FHHt are treated by low doses of thiazide diuretic, and it mirrors Gitelman syndrome which features the inverse phenotype of hypotension, hypokalemic metabolic alkalosis, and hypocalciuria. Gitelman syndrome is caused by loss of function mutations in the thiazide-sensitive Na/Cl cotransporter (NCC); however, FHHt patients do not have mutations in the SCL12A3 locus encoding NCC. Instead, mutations have been identified in genes that have revealed a key signalling pathway that regulates NCC and several other key transporters and ion channels in the kidney that are critical for BP regulation. This is the WNK kinase signalling pathway that is the subject of this review.